Growth and yield of several rice varieties on alluvial soil using N, P, and K fertilizers - Radian; Abdurrahman, Tatang; Mahmudi; Safriadi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Adaptive varieties and N, P, and K fertilization can increase rice productivity. The study aimed to determine the effect of N, P, and K fertilizer dosages on the growth and yield of several rice varieties on alluvial soil. The research was conducted in Kubu Raya Regency, West Kalimantan, from March to October 2023. The method used a factorial randomized complete block design with three replications. The first factor was rice varieties (Argo Pawan, Bima Saputra, Inpari 43, Padang, and Tropiko). The second factor was N, P, and K fertilization (150 kg N ha-1+ 100 kg P2O5 ha-1 + 100 kg K20 ha-1; 300 kg N ha-1 + 200 kg P2O5 ha-1 + 200 kg K20 ha-1; 450 kg N ha‑1 + 300 kg P2O5 ha-1 + 300 kg K20 ha-1). The Tropiko variety had the highest plant height compared to other varieties. The Inpari 43 variety produced the highest maximum number of tillers. Furthermore, the Inpari 43 and Tropiko varieties were the best treatments for producing the number of productive tillers and grain weight per plot. The N, P, and K fertilizer dosage of 300 kg N ha-1 + 200 kg P2O5 ha-1 + 200 kg K20 ha-1 was the best treatment in producing growth and yields of rice plants based on the variables of maximum number of tillers, number of productive tillers, and grain weight per plot. Keywords: adaptive varieties; rice productivity; soil fertility